Investigating differentiation: exploring the impact of task difficulty labelling on students’ mathematics performance - Herset, Maria; El Ghami, Mohamed; Hessen Bjerke, Annette (NOMAD Nordic Studies in Mathematics Education, 2025)
This study investigated the effect of task difficulty labelling on students’ mathematics performance. Lower secondary school students (n = 436) participated in an experimental study in which the control group received three similar tasks without labels and the experimental groups received the same tasks labelled as easy, medium and difficult. The findings indicate that the students in the control group outperformed the students assigned tasks labelled as difficult. Additionally, the students’ performance was worse when solving tasks labelled difficult compared to when they were given similar tasks labelled easy or medium, but the differences are not significant. We strongly advise exercising prudence when assigning tasks labelled difficult.